Analisis Pengaruh Penggunaan AAU pada Swap RRU terhadap Kualitas Layanan Telekomunikasi di Wilayah Pusdikom Cibeureum Cimahi - H.D, Ni Ketut; Ayurisa Monaretta Konadi; Fauzia Haz (EPSILON: Journal of Electrical Engineering and Information Technology, 2023)
Telecommunications technology continues to undergo advancements. The enabler of communication in the field of telecommunications is the telecommunications equipment installed on a BTS tower. These devices are constantly being updated to improve the service provided by the provider to meet the needs of customers. One of the network technologies currently used is 4G LTE. To enhance the network service, one of the measures taken is performing a swap or upgrade of the telecommunications equipment on a BTS tower. The upgrade of telecommunications equipment is also influenced by the population in the vicinity of the BTS tower. This allows for the replacement of telecommunications devices with ones that have broader coverage and better signal quality. This research, we discuss the issue of network capacity shortage in the Cibeureum area, South Cimahi. This is indicated by the addition of AAUs to the BTS tower in Pusdikom, Cibeureum. This research found data that South Cimahi is the most densely populated area in the city compared to other districts. Therefore, the addition of AAUs is highly effective for this issue. It is known that the AAUs are added to replace the RRUs on the tower. This is because the capacity and transmission channels of AAUs are greater than RRUs. The addition of AAU with 32T32R specifications to the tower improves signal quality with the following parameter values: RSRP(dbm): -68, -72, -76; RSRQ(db): -11, -10, -10; and SNR(db): 1, 1, 4. These values are categorized as good, indicating that the addition of AAU to the tower can effectively increase network capacity and transmission channels, thereby improving network quality in the area.